ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KERJA PEREMPUAN NIKAH DI KOTA PEKANBARU - Fitri Sulistriyanti; Lapeti Sari; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze the influence of respondent education variable, husband income, and number of family, on married woman labor participation measured by the level of wages. The analytical tool that used in this research is multiple linear regression by SPSS 21,0. The data wich used is primary data collected by interviews with 100 respondents in Pekanbaru. The result of test F (simultaneously) with three independent variables : respondent education, husband income, and number of family have a significant influence on the dependent variable (married woman labor participation). The result of R Square (R2) of the independent variables simultan can explain the dependent variable, and the rest is influenced by the other variables wich are not examined in this research. T test (partial) shows that each independent variables (responden education, husband income, and number of family) have a significant influence on the dependent variable (married woman labor participation).Keywords : Married woman labor participation, respondent education, husband income, and number of family.